On the mechanism of Mn partitioning during intercritical annealing in medium Mn steels. (15th February 2022) - Guo, Qinyi; Yen, Hung-Wei; Luo, Haiwen; Ringer, Simon P.
Abstract: To understand how solute Mn in the reverted austenite is able to rapidly partition to near-equilibrium concentration values during the typically short intercritical annealing (IA) of medium Mn steels (MMS), reverse transformation kinetics were simulated numerically. We applied a variety of assumptions both for the diffusivity of Mn in austenite and martensite/ferrite and for the interface mobility. These simulation results were compared with measurements of the Mn concentration gradient near the interface as measured by atom probe tomography. Our inclusion of an interface mobility term, with physical origins from the interfacial dissipation energy, reduced the interphase interface migration rate, resulting in much higher values of the interfacial Mn concentration than in the scenario whereby diffusion-controlled transformation kinetics dominate. These results have led us to propose that the austenite/ferrite interface exhibits a fluctuational interface mobility during IA. This new phenomenological description of the interface migration achieves the best fit to the measured fluctuations of the Mn concentration gradients near the interface. We suggest that the fluctuational mobility arises from encounters between the interface and the regions of crystal containing precipitates and/or microstructural defects. Abstract : Image, graphical abstract